For a reflection in neuroeducation – brain-based learning method principles and its application in higher education level - Veiga-Branco, Augusta (2018)
Recent neuroscience literature presents interesting and motivating contributions to pedagogical field, in emotion and motivation (Turner, Chandler, & Heffer, 2009, Veiga‐ Branco, 2011, Fonseca, 2014, 2016, Everaert, Opdecam & Maussen, 2017), attention, learning and memory (Ma et al., 2018). Articles and learning manuals appeared with new conceptions, and from these contributions emerged the proposal of Brain‐based learning and educational neuroscience (MB‐BL/EN), (Tokuhama‐Espinosa, 2008, Willis, 2010, Liu & Chiang, 2014, Ramos, 2014, Edelenbosch et al., 2015) as pedagogical practice hypothesis in Neuroscience, as way of promoting learning and facilitating memories